Multivalent Binding of Formin-binding Protein 21 (FBP21)-Tandem-WW Domains Fosters Protein Recognition in the Pre-spliceosome - Klippel, Stefan (American Society for Biochemistry and Molecular Biology, 2011)
The high abundance of repetitive but nonidentical proline-rich sequences in spliceosomal proteins raises the question of how these known interaction motifs recruit their interacting protein domains. Whereas complex formation of these adaptors with individual motifs has been studied in great detail, little is known about the binding mode of domains arranged in tandem repeats and long proline-rich sequences including multiple motifs. Here we studied the interaction of the two adjacent WW domains of spliceosomal protein FBP21 with several ligands of different lengths and composition to elucidate the hallmarks of multivalent binding for this class of recognition domains. First, we show that many of the proteins that define the cellular proteome interacting with FBP21-WW1-WW2 contain multiple proline-rich motifs. Among these is the newly identified binding partner SF3B4. Fluorescence resonance energy transfer (FRET) analysis reveals the tandem-WW domains of FBP21 to interact with splicing factor 3B4 (SF3B4) in nuclear speckles where splicing takes place. Isothermal titration calorimetry and NMR shows that the tandem arrangement of WW domains and the multivalency of the proline-rich ligands both contribute to affinity enhancement. However, ligand exchange remains fast compared with the NMR time scale. Surprisingly, a N-terminal spin label attached to a bivalent ligand induces NMR line broadening of signals corresponding to both WW domains of the FBP21-WW1-WW2 protein. This suggests that distinct orientations of the ligand contribute to a delocalized and semispecific binding mode that should facilitate search processes within the spliceosome.